Distinct roles of immunoreceptor tyrosine‐based motifs in immunosuppressive indoleamine 2, 3‐dioxygenase 1. Issue 1 (30th September 2016) - Albini, Elisa; Rosini, Verdiana; Gargaro, Marco; Mondanelli, Giada; Belladonna, Maria L.; Pallotta, Maria Teresa; Volpi, Claudia; Fallarino, Francesca; Macchiarulo, Antonio; Antognelli, Cinzia; Bianchi, Roberta; Vacca, Carmine; et al.
Abstract: The enzyme indoleamine 2, 3‐dioxygenase 1 (IDO1) catalyses the initial, rate‐limiting step in tryptophan (Trp) degradation, resulting in tryptophan starvation and the production of immunoregulatory kynurenines. IDO1's catalytic function has long been considered as the one mechanism responsible for IDO1‐dependent immune suppression by dendritic cells (DCs), which are master regulators of the balance between immunity and tolerance. However, IDO1 also harbours immunoreceptor tyrosine‐based inhibitory motifs, (ITIM1 and ITIM2), that, once phosphorylated, bind protein tyrosine phosphatases, (SHP‐1 and SHP‐2), and thus trigger an immunoregulatory signalling in DCs. This mechanism leads to sustained IDO1 expression, in a feedforward loop, which is particularly important in restraining autoimmunity and chronic inflammation. Yet, under specific conditions requiring that early and protective inflammation be unrelieved, tyrosine‐phosphorylated ITIMs will instead bind the suppressor of cytokine signalling 3 (SOCS3), which drives IDO1 proteasomal degradation and shortens the enzyme half‐life. To dissect any differential roles of the two IDO1's ITIMs, we generated protein mutants by replacing one or both ITIM‐associated tyrosines with phospho‐mimicking glutamic acid residues. Although all mutants lost their enzymic activity, the ITIM1 – but not ITIM2 mutant – did bind SHPs and conferred immunosuppressive effects on DCs, making cells capable of restraining an antigen‐specific response in vivo . Conversely, the ITIM2 mutant would preferentially bind SOCS3, and IDO1's degradation was accelerated. Thus, it is the selective phosphorylation of either ITIM that controls the duration of IDO1 expression and function, in that it dictates whether enhanced tolerogenic signalling or shutdown of IDO1‐dependent events will occur in a local microenvironment.